Middle Triassic remnant of the Palaeo‐Tethys Ocean, central Tibet: Constraints from the Pianshishan retrograded eclogite‐type rocks. Issue 8 (19th April 2022) - Lu, Rukui; Li, Yang; Sun, Shaolin; Liu, Yiming; Nan, Guowei; Cui, Haifeng; Huang, Yuanyi
Abstract : The high‐pressure and low‐temperature metamorphic rocks constitute the important parts of the Longmu Co‐Shuanghu suture zone (LSS) in Tibet, providing a natural window for unveiling the tectonic evolution of the Palaeo‐Tethys Ocean. In this contribution, geochemical studies, including the whole‐rock geochemistry, Sr‐Nd isotopes and zircon U–Pb geochronology, were performed on the Pianshishan garnet amphibolites and retrograded eclogites, to reconstruct the genesis of the protoliths and to reveal tectonic evolution of the Longmu Co‐Shuanghu Palaeo‐Tethys Ocean (LSPTO). The garnet amphibolites show characteristics similar to the retrograded eclogites, representing different degrees of retrograde metamorphism of the Pianshishan eclogites. The protoliths of garnet amphibolites and retrograded eclogites are alkaline basalts, with geochemical characteristics similar to ocean island basalts (OIB) without Nb, Ta or Ti negative anomalies. Furthermore, geochemical data imply that the protoliths were formed by fractional crystallization of the magma derived from partial melting of garnet lherzolites without crustal contamination. The parental magma was probably generated in a relatively depleted but heterogeneous asthenosphere mantle source. Their protoliths erupted as a seamount within the LSPTO. Garnet amphibolites and retrograded eclogites yielded zircon U–Pb weighted mean ages of 240.2 ± 1.7 Ma and 239.1 ± 2.7 Ma, respectively. Combining with previous studies, we suggest that the LSPTO remained open in the Pianshishan area during the Middle Triassic, and the whole ocean might be gradually closed during the Early to Late Triassic. The small remnant ocean basin during the Middle Triassic can well explain a rapid evolution of the Pianshishan eclogite‐type rocks, that is, from generation to eclogite‐facies metamorphism and then to exhumation‐related retrograde metamorphism within ~19 Myr. Abstract : Protoliths of the Pianshishan garnet amphibolites and retrograded eclogites were formed at ~239–240 Ma, with OIB geochemical signatures. A remnant of the LSPTO existed in the Pianshishan area during Middle Triassic. The rocks underwent a rapid evolution (within ~19 Myr) from generation to peak metamorphism and then to retrograde metamorphism.